'Surrender to nature': Worldviews and rituals of the small-scale coastal fishers of Bangladesh. (June 2018) - Deb, Apurba Krishna
Abstract: Small-scale fishing in the Bay of Bengal using non-motorized, wooden motorized and mechanized boats without basic safety devices is a risky venture. Fishers developed a long tradition of adaptation to the dynamics of the unpredictable nature of the marine ecosystem. The empirical findings presented in this article are primarily based on a two-year long ethnographic study with the caste-based Hindu coastal fishers of Thakurtala fishing village, Moheskhali Island, Cox's Bazar. The worldviews and popular beliefs associated with fish and fishing epitomize a rich cultural history of fish-loving Bengali societies. The article examines pragmatically obvious notions of luck, risks, and socio-political implications behind observances of rituals in the coastal fishing villages. Observances of rituals at both domestic and community ambits are perceived to improve luck, reduce anxiety level associated with marine fishing, and reinforce pre-voyage psychological preparedness of the sea-faring fishers and their family members. It documents the roles of fish and fishing related worldviews in rural Bengali societies along with the pre-voyage and post-voyage activities and rituals observed by coastal fishers. Some ritual practices are characterised by interfaith fusion, and hence, their observance would positively add to the foundations of secular practices, humanism, and mutually benefitting existential philosophy in rural societies. This ethnographic narrative also examines fishing cultures' comprehensive articulations of natural and unnatural elements of marine ecosystem within the broader framework of maritime anthropology.